Information Systems Supporting The Process of Educating Leaders-Managers In Security Decision-Making - Marian KOPCZEWSKI; Paweł OLBRYCHT (Communications of International Proceedings, 2021)
Based on the observation of everyday functioning, it can be observed that Artificial Intelligence plays an increasingly important role in social life. It is also noticeable in the decision-making process, including in the area of security. The article aims to indicate the need for closer, practical interest in IT tools, by analyzing selected artificial intelligence systems, which can support the educational and decision-making process in context of security. The problem presented in the article was analyzed by studying practical solutions applied by military higher education institutions. It was primarily concerned with finding answers to the questions: – What information systems can be most effective in the processes of teaching and command/management and decision support processes? – Is there a specific order of introducing individual solutions? – Are the benefits of using modern concepts, presented in literature, possible to achieve in Polish educational reality? In the research process, qualitative research methods were used, including the analysis of literature sources (content analysis technique). The results show that Artificial Intelligence helps humans make decisions in many areas of life and that they are the most effective in teaching and command/management and decision support processes, also in context of security.
Keywords: Systems; Education; Decision; Security